Prokrastinasi Akademik Mahasiswa Program Studi PGSD Di Masa Pandemi Covid-19 - Musfirah; Nur Halim AR; Suciani Latif (KONSELING: Jurnal Ilmiah Penelitian dan Penerapannya, 2022)
The COVID-19 pandemic affects various lines of life, not only in terms of health and the economy but almost everything, one of which is education. The existence of the COVID-19 pandemic requires educational activities, especially teaching and learning activities to be carried out from home. Students are not required to adapt to these conditions. All learning activities are carried out from home using available learning applications. Learning from home is a challenge for students of the PGSD study program. Students must manage time so that they can still study even though it is done online. However, some students often postpone their assignments, are late in submitting assignments and spend more time doing more fun things. Behavior that often delays tasks, especially academic tasks, is called academic procrastination. Academic procrastination will be a problem in itself if it is not handled properly.